2017
DOI: 10.3892/mmr.2017.6755
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of miR-155 is associated with the differentiation of CD8+ T cells in patients with HIV-1

Abstract: The differentiation and response ofCD8+ T cells is vital in host defense against human immunodeficiency virus type 1 (HIV-1). MicroRNA (miR)‑155 is an important regulator of T cell differentiation. However, the profile of miR-155 in HIV‑1 infected individuals and its association with CD8+ T cell differentiation remain to be fully elucidated. The present cross‑sectional study was performed involving 63 HIV‑1‑infected patients undergoing highly active antiretroviral therapy (HAART), 31 HAART‑naïve patients and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Atherosclerosis, an inflammatory disease of the arterial wall characterized by the formation of white blood cell-rich plaques in the intimal layer of large and medium-sized arteries, is induced and maintained by the inflow, proliferation and activation of immune cells (33,34). miR-155 is reported to play a role in activating immune response and promoting T cell activation (35,36), indicating that miR-155 may be involved in the enhancement of the immune response during atherosclerosis. Therefore, we preliminarily confirmed that miR-155 promoted the development of atherosclerosis through targeted inhibition of Bmal1.…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis, an inflammatory disease of the arterial wall characterized by the formation of white blood cell-rich plaques in the intimal layer of large and medium-sized arteries, is induced and maintained by the inflow, proliferation and activation of immune cells (33,34). miR-155 is reported to play a role in activating immune response and promoting T cell activation (35,36), indicating that miR-155 may be involved in the enhancement of the immune response during atherosclerosis. Therefore, we preliminarily confirmed that miR-155 promoted the development of atherosclerosis through targeted inhibition of Bmal1.…”
Section: Discussionmentioning
confidence: 99%
“…It is also described as a modulator of various aspects and steps of innate and adaptive immune responses [ 40 ]. Abundantly expressed in reactivated cells, its expression is required for optimal CD8+ T cell responses to counter viral replication [ 41 , 42 ]. The elevated expression of miR-146 and miR-155 in EVs of viremic patients could serve to inform and protect surrounding cells from HIV infection and help manage host-dependent factors and cellular pathways important for viral replication.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of this miRNA is positively associated with the proportions of effector and effector memory CD8+ T cells, while showing an inverse correlation with the proportions of naïve and central memory CD8+ T cells. Overall, the upregulation of miRNA-155 expression in CD8+ T cells of PLWH is associated with the differentiation of these cells [ 85 ]. The NFκB:miRNA-155 pathway can stimulate an immune response in monocyte-derived macrophages following the suppression of CCL2 [ 86 ].…”
Section: Non-coding Rnas In the Neuropathogenesis Of Hiv Infection An...mentioning
confidence: 99%